Seven interferon gamma response genes serve as a prognostic risk signature that correlates with immune infiltration in lung adenocarcinoma - Yao, Boyang (Aging (Albany NY), 2021)
Interferon-gamma (IFN-γ) plays a complex role in modulating tumor microenvironment during lung adenocarcinoma (LUAD) development. In order to define the role of IFN-γ response genes in LUAD progression, we characterized the gene expression, mutation profile, protein-protein interaction of 24 IFN-γ response genes, which exhibited significant hazard ratio in overall survival. Two subgroups of LUAD from the TCGA cohort, which showed significant difference in the survival rate, were identified based on the expression of these genes. Furthermore, LASSO penalized cox regression model was used to derive a risk signature comprising seven IFN-γ response genes, including CD74, CSF2RB, PTPN6, MT2A, NMI, LATS2, and PFKP, which can serve as an independent prognostic predictor of LUAD. The risk signature was validated in an independent LUAD cohort. The high risk group is enriched with genes regulating cell cycle and DNA replication, as well as a high level of pro-tumor immune cells. In addition, the risk score is negatively correlated with the expression of immune metagenes, but positively correlated with DNA damage repair genes. Our findings reveal that seven-gene risk signature can be a valuable prognostic predictor for LUAD, and they are crucial participants in tumor microenvironment of LUAD.